2017
DOI: 10.1371/journal.pone.0188500
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical correlates of human level-ground, slope, and stair walking

Abstract: This study investigated electrocortical dynamics of human walking across different unconstrained walking conditions (i.e., level ground (LW), ramp ascent (RA), and stair ascent (SA)). Non-invasive active-electrode scalp electroencephalography (EEG) signals were recorded and a systematic EEG processing method was implemented to reduce artifacts. Source localization combined with independent component analysis and k-means clustering revealed the involvement of four clusters in the brain during the walking tasks:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 62 publications
5
50
0
Order By: Relevance
“…As such, ERS and ERD reflect an induced response of ongoing activity rather than an additive response and would hence not be accompanied by phase locked activity (Tallon-Baudry et al 1996). As the changes in spectral power observed here closely resemble those previously reported in ambulatory EEG studies (Artoni et al 2017; Bradford et al 2016; Bruijn et al 2015; Bulea et al 2015; Cheron et al 2012; Gwin et al 2011; Knaepen et al 2015; Luu et al 2017; Oliveira et al 2017b; Severens et al 2012), this may require a broader reinterpretation of the cortical dynamics during walking.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As such, ERS and ERD reflect an induced response of ongoing activity rather than an additive response and would hence not be accompanied by phase locked activity (Tallon-Baudry et al 1996). As the changes in spectral power observed here closely resemble those previously reported in ambulatory EEG studies (Artoni et al 2017; Bradford et al 2016; Bruijn et al 2015; Bulea et al 2015; Cheron et al 2012; Gwin et al 2011; Knaepen et al 2015; Luu et al 2017; Oliveira et al 2017b; Severens et al 2012), this may require a broader reinterpretation of the cortical dynamics during walking.…”
Section: Discussionsupporting
confidence: 85%
“…The cortical power fluctuations during overground and treadmill walking observed in this study closely resemble those previously reported in ambulatory EEG studies conducted on a treadmill. A number of studies found increased power over sensorimotor cortical areas at the end of stance and during double support, and decreased power during the swing/single support phase (Artoni et al 2017; Bradford et al 2016; Bruijn et al 2015; Bulea et al 2015; Cheron et al 2012; Gwin et al 2011; Knaepen et al 2015; Luu et al 2017; Oliveira et al 2017b; Severens et al 2012). Notably, one previous study (Bulea et al 2015) reported similar changes in cortical power to those in the current study during walking on a user-driven treadmill, a condition which simulates overground walking more closely than walking on a standard, motorized treadmill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting finding was that the largest maximum distances, among the three ICs of interest, occurred in the primary somatosensory cortex, which is an area frequently discussed in the EEG studies related to walking [8,9]. A previous study found that tangential sources near the boundary of the cortex were more sensitive to electrode location errors, which could explain the larger maximum distances for the dipole at the primary somatosensory cortex compared to a dipole deeper within the cortex such as the anterior cingulate [5].…”
Section: Discussionmentioning
confidence: 97%
“…We analyzed the influence of the fiducial shifts on all twenty-three ICs but picked three to illustrate dipole location alterations in detail: 1) the anterior cingulate, 2) the primary somatosensory cortex, and 3) the premotor cortex. Previous studies have shown that these three areas are active in locomotion and error monitoring [8,9].…”
Section: A Source Estimation and Dipole Fittingmentioning
confidence: 99%